Pivotal Clinical Study to Evaluate the Safety and Effectiveness of the MANTA Vascular Closure Device During Percutaneous EVAR and TEVAR Procedures. (June 2020) - Krajcer, Zvonimir; Wood, David A.; Strickman, Neil; Bernardo, Nelson; Metzger, Chris; Aziz, Mark; Bacharach, J. Michael; Nanjundappa, Aravinda; Campbell, John; Lee, Jason T.; Dake, Michael D.; Lumsden, Alan; et al.
Purpose: To evaluate the safety and effectiveness of the MANTA percutaneous vascular closure device in patients undergoing percutaneous endovascular aneurysm repair (PEVAR) or thoracic endovascular aortic repair (TEVAR).Materials and Methods: The SAFE MANTA Study ( ClinicalTrials.gov identifier NCT02908880) was a prospective, single-arm, multicenter trial in patients undergoing endovascular interventions using large-bore sheaths (transcatheter aortic valve replacement, PEVAR, or TEVAR) at 20 sites in North America. Patient selection intended to test the MANTA device in populations without morbid obesity, severe calcification, or a severely scarred femoral access area. Of the 263 patients enrolled in the primary analysis cohort, 53 (20.2%) patients (mean age 74.9±8.9 years; 41 men) underwent PEVAR (n=51) or TEVAR (n=2) procedures and form the cohort for this subgroup analysis. Per protocol a single MANTA device was deployed in all PEVAR/TEVAR cases.Results: The mean time to hemostasis in the PEVAR/TEVAR cohort was 35±91 seconds, with a median time of 19 seconds vs 24 seconds in the overall SAFE MANTA population. The MANTA device met the definition for technical success in 52 (98%) of 53 PEVAR/TEVAR cases compared with 97.7% in the overall SAFE MANTA population. One (1.9%) major complication (access-site stenosis) occurred in this subgroup compared to 14 (5.3%) events in the SAFE population. In the PEVAR/TEVAR group, 1 pseudoaneurysm was noted prior to discharge, another at 30-day follow-up, and one at 60 days. One (1.9%) of the 3 minor pseudoaneurysms was treated with ultrasound-guided compression and the other 2 required no treatment.Conclusion: The MANTA device demonstrated a short time to hemostasis and low complication rates compared with published literature results of other percutaneous closure devices. Time to hemostasis and complication rates were comparable between the PEVAR/TEVAR patients and the full SAFE MANTA study cohort. The MANTA device provides reliable closure with a single percutaneous device for PEVAR/TEVAR procedures.